Cracks and Fault Lines: Foreign Policy Orientations of Western Balkan Capitals in the Context of the Ukrainian Crisis - E. S. Arlyapova; E. G. Ponomareva (Vestnik MGIMO-Universiteta)
The Ukrainian crisis has reverberated throughout the troubled region of the Balkans in Southern Europe, exposing deep-seated cracks and fractures that have long characterized this geopolitical area. The crisis has not only highlighted divisions between local states but also between communities and ethno-religious groups. In many cases, these intraregional contradictions are exacerbated by external actors and their demands. This article examines the foreign policy priorities and orientations of Western Balkan capitals within the "five plus one" format states (Albania, Bosnia and Herzegovina, Montenegro, North Macedonia, Serbia, and the partially recognized "Republic of Kosovo") in light of the crisis in Ukraine, illustrating the interplay between regional dynamics and international crises.Drawing on a wide range of sources, including official documents and opinion polls on foreign policy, this paper identifies regional discrepancies in the perception and assessment of the ongoing Ukrainian conflict. The study employs a historical-systemic approach and neorealism principles to discern potential directions for political institutions in the external context. The analysis reveals that a fragile "balance of threats" persists in the region, heavily influenced by the goals and interests of external actors such as the EU, NATO, the United States, Russia, and to a lesser extent, China and Turkey.The military and political disengagement observed in 2022 mirrors the alignment of local players witnessed in 2014, but with a significant difference: the West now expects all participants in the "five plus one" format to fully adhere to their joint foreign policy, including implementing restrictive measures against the Russian Federation. This presents a challenging dilemma for Belgrade and Banja Luka, as they cannot overlook the widespread support for Russia's actions among the Serbian population. Any anti-Russian steps taken by local authorities may lead to serious internal political conflicts in both Serbia and Republika Srpska, with far-reaching implications for regional stability.